Improving Students' Eco-literacy through the Development of Electronic Interactive Teaching Materials on Climate Change - Rubini, Bibin; Pursitasari, Indarini Dwi; Suriansyah, Muhammad Iqbal; Ramadhanti, Ghina Nisrina; Rachman, Indriyani (Jurnal Penelitian dan Pembelajaran IPA, 2023)
This study aimed to produce electronic interactive teaching material that can build students’ eco-literacy of climate change. This study used ADDIE design, which began with analyzing needs as a reference and consideration for compiling electronic interactive teaching materials on climate change (e-ITMCC). This study began with analyzing needs as a reference in designing e-ITMCC. Furthermore, a feasibility test was carried out on the e-ITMCC design. Feasibility tests are conducted by material content and multimedia experts using expert judgment sheets. Research instruments use tests, questionnaires, and observations. e-ITMCC was declared suitable for use based on expert judgment and the acquisition of CVR and CVI of teacher assessment results. This e-ITMCC effectively applies them in science learning in junior high school class VII. The implementation results showed that the student's eco-literacy increased after studying climate change with e-ITMCC. Students also responded very well to the use of these teaching materials.